Prevalence and risk factors of dry eye symptoms in Jazan Province, Saudi Arabia: a cross-sectional study - Najmi, Hatim Hassan; Tubayqi, Abdulrahman Mohsen; Bakri, Sultan Mousa; Alsharif, Abdullah Meshal (Frontiers in Ophthalmology, 2025)
PurposeDry eye syndrome (DES) is characterized by tear film and ocular surface disruptions. Symptomatic DES, one of the most common ocular diseases, reduces the quality of life. This study aimed to evaluate the prevalence of and possible risk factors for DES in the Jazan region of Saudi Arabia.MethodsThis observational, cross-sectional study was conducted between October 2018 and May 2023. This study was conducted with 1061 participants using an online survey that included questions on sociodemographic characteristics, dry eye symptoms, possible factors related to dry eye, and chronic comorbidities. Dry eye symptoms were evaluated using the Ocular Surface Disease Index (OSDI).ResultsThe overall prevalence of dry eye symptoms was 59.9%, with 19.7% of the respondents having mild, 14.0% having moderate, and 26.2% having severe dry eye symptoms. A statistically significant difference in dry eye symptoms prevalence was observed between males and females (X2 = 54.167; p = 0.000), with females (68.4%) being more commonly affected than males (52.2%). Moreover, Female participants were 1.78 times more likely to develop DES than males, and this association remained statistically significant after adjustment (OR = 1.78; 95% CI: 1.37–2.31). Smoking (p = 0.44), computer use (p = 0.87), and mobile phone use (p = 0.69), were not significantly associated with DES prevalence.ConclusionDry eye symptoms are highly prevalent in Jazan Province, Saudi Arabia, affecting nearly 60% of the population. Female sex was a significant risk factor, while screen time and smoking were not. However, as the study relied on self-reported symptoms without objective clinical tests, the findings may not fully reflect disease prevalence. These results highlight the need for targeted screening and public health efforts in high-risk groups.